Effect of Temperature on Plasma-Assisted Catalytic Cracking of Palm Oil into Biofuels - Istadi, I.; Riyanto, Teguh; Buchori, Luqman; Anggoro, Didi Dwi; Saputra, Roni Ade; Muhamad, Theobroma Guntur (International Journal of Renewable Energy Development, 2020)
Plasma-assisted catalytic cracking is an attractive method for producing biofuels from vegetable oil. This paper studied the effect of reactor temperature on the performance of plasma-assisted catalytic cracking of palm oil into biofuels. The cracking process was conducted in a Dielectric Barrier Discharge (DBD)-type plasma reactor with the presence of spent RFCC catalyst. The reactor temperature was varied at 400, 450, and 500 ÂºC. The liquid fuel product was analyzed using a gas chromatography-mass spectrometry (GC-MS) to determine the compositions. Result showed that the presenceof plasma and catalytic role can enhance the reactor performance so that the selectivity of the short-chain hydrocarbon produced increases. The selectivity of gasoline, kerosene, and diesel range fuels over the plasma-catalytic reactor were 16.43%, 52.74% and 21.25%, respectively, while the selectivity of gasoline, kerosene and diesel range fuels over a conventional fixed bed reactor was 12.07%, 39.07%, and 45.11%, respectively. The increasing reactor temperature led to enhanced catalytic role of cracking reaction,particularly directing the reaction to the shorter hydrocarbon range. The reactor temperature dependence on the liquid product components distribution over the plasma-catalytic reactor was also studied. The aromatic and oxygenated compounds increased with the reactor temperature.Â©2020. CBIORE-IJRED. All rights reserved